ANALISIS KEPUASAN KONSUMEN PADA HOTEL SMIP KRIDA WISATA BANDAR LAMPUNG - Irianto Loka (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2012)
Employers who do business in the field of hotel services they should be able to competeclosely with each other. Who is good at predicting the possibilities that will happen in the future inservice businesses and has been prepared to spend the strategies to address the possibility he willbe able to compete in the business services.One hotel tried to boost the quality of services delivered to achieve customer satisfaction isHotel SMIP Tourism Activities Belfast, this hotel is a place of hospitality science education to educatethe SMIP (Tourism Industry High School) for a diploma in Hospitality and tourism businesses.Unfortunately the end of the hotel considers SMIP Krida Tourism can not provide good service tomeet customers' needs. That's because the candidates still see where the hotel guests Krida Travelis still managed by students and as a place of learning.The purpose of this study was to measure how much influence Against Quality of ServiceCustomer Satisfaction On Travel Hotels SMIP Krida Bandar Lampung